Pengaruh Penggunaan Media Polypad Berbasis Web terhadap Hasil Belajar Materi Jaring-Jaring Bangun Ruang Siswa Kelas V UPTD Socah 1 - Taqyuki Izuki; Echa Khofifatul Ma’Rifah; Ika Dian Rahmawati (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This research examines the effectiveness of web-based Polypad media in enhancing mathematics learning outcomes for fifth-grade elementary school students on geometric nets topic. Polypad is a free, web-accessible interactive mathematics platform developed by Mathigon that enables students to visually and exploratively construct flat shapes into three-dimensional nets, covering cubes, rectangular prisms, cones, square pyramids, triangular prisms, and cylinders. The use of this technology-based medium is expected to deepen students' conceptual grasp of geometry by offering learning experiences that are more hands-on, engaging, and context-rich in comparison to traditional classroom instruction. This study employed a pre-experimental approach utilizing a one-group pretest-posttest design. The participants involved consisted of 28 fifth-grade students at UPTD SDN Socah 1 Bangkalan, with data collected through a 10-item multiple-choice learning achievement instrument. The magnitude of learning progress was measured using the Normalized Gain (N-Gain) index, while a paired sample t-test was applied to evaluate whether the difference in scores obtained before and after the intervention carried statistical significance. The analysis revealed that the class average climbed from 56.4 at the pretest stage to 73.2 at the posttest stage, yielding an N-Gain value of 0.40 which falls within the moderate category. The t-test results further confirmed that the improvement was statistically significant, suggesting that Polypad media exerts a considerable positive influence on student learning outcomes.